1979
DOI: 10.1136/adc.54.6.409
|View full text |Cite
|
Sign up to set email alerts
|

Clinical events relating to intraventricular haemorrhage in the newborn.

Abstract: SUMMARY Continuous measurements of arterial pressures, heart rates, respiratory movements, and respiratory rates were made from birth in 44 infants at risk from intraventricular haemorrhage (IVH). 17 babies died with IVH, in 10 of whom the event was timed objectively. Events in these babies were compared with survivors of similar birthweights, gestational ages, severity of birth asphyxia, and severity of hyaline membrane disease (HMD). IVH followed severe HMD and was associated with cessation of the babies' ow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In this population, low postnatal BP has been linked to the development of intraventricular hemorrhage (IVH) (1)(2)(3)(4)(5)(6)(7)(8), ischemic cerebral lesions (3), adverse neurodevelopmental outcome (7,9,10), and neonatal mortality (3,4,7,10). BP regulation in preterm infants is complex and poorly understood, and several perinatal factors have been shown to influence postnatal BP in preterm infants.…”
mentioning
confidence: 99%
“…In this population, low postnatal BP has been linked to the development of intraventricular hemorrhage (IVH) (1)(2)(3)(4)(5)(6)(7)(8), ischemic cerebral lesions (3), adverse neurodevelopmental outcome (7,9,10), and neonatal mortality (3,4,7,10). BP regulation in preterm infants is complex and poorly understood, and several perinatal factors have been shown to influence postnatal BP in preterm infants.…”
mentioning
confidence: 99%
“…Accordingly, periventricular hemorrhage may result from abrupt hyperperfusion whereas periventricular leukomalacia has been related to ischemia (1)(2)(3)(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…TSIANTOS et al [21] routinely labeled erythrocytes of neonates with Chromium 51 within the first few hours of life and found that 60% of the hemorrhages took place between 15 and 48 hours of age. FUJIMURA et al [9] using hemoglobin as a marker, observed that infants less than 28 week's gestation were more likely to sustain PIVH in the first 24 hours of life than infants of greater gestational age. The authors concluded that these early hemorrhages are common in very low birth weight infants and that they are probably related to adverse parinatal factors.…”
Section: Discussionmentioning
confidence: 99%